Formação docente em cursos de licenciatura da UFSM: sobre políticas curriculares e discussões de gênero e de sexualidades - Correia, Daiana Godinho Martins (2021)
This research was developed in the Program of Post-Graduation in Public Policies and School Management (PPGEE) – Professional master’s degree at the Federal University of Santa Maria, in the line of research “Policies and School Management – LP1”. It aimed to understand how students of teachers’ initial training at UFSM think about gender identities and sexual orientation, given their acting as future teachers. Initially, the systematization of the studies about the theme was conducted. In the second moment, the Public Policies that aim to insert the theme on universities and basic education were brought. We also seek for perceiving how the curriculum of teachers’ initial training is pervaded by its subject. The research was reasoned in a qualitative approach, involving a query in documents and empirical data. An online survey was used as a method of data collection, distributed to the students who participate in programs such as PIBID and Pedagogical Residence in the teaching courses at UFSM. In the seek for understanding the data, the Discourse Analysis was chosen, from which we cast some elements to the analysis: the discourses produced by PCC’s degrees, the discourses from the subjects about the relevance of the thematic to the teaching acting and the relation between the formation and practice in educative contexts. After the analysis, we perceived that the curriculum of teachers’ initial training at UFSM brings some courses about gender identity and sexual orientation, but there are some gaps in this formation. So, it was proposed as an educational product a course to students of licentiate degrees from UFSM, to promote reflexive moments, knowledge and experience exchange so the school and the teachers can accomplish their social role of formatting critical subjects, lacking of prejudice and that can be producers of equality and respect.